Development of marketing technologies in the field of tourism - Nesterov, Dmitriy; Pererva, Vyacheslav; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
It has been proven that the development of tourism, like no other sector of the economy, stimulates the creation of jobs and the development of small businesses, redistributes resources between countries, has a stimulating effect on such sectors of the economy as transport, communication, the sphere of services, trade, construction, production of goods of public consumption, is one of the most promising directions of structural restructuring of the economy of Ukraine
Розвиток маркетингових технологій у сфері туризму
Keywords: tourism business; resources; partners; features; agencies; services